ANALISIS PENGARUH PENATAAN ORGANISASI LIPI TERHADAP KEBAHAGIAAN ASN PENDUKUNG IPTEK DI LINGKUNGAN LIPI - Lia Fitrianingrum; Dina Lusyana; Debby Lellyana (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2020)
This research is based on a phenomenon that LIPI, as the largest research institution in Indonesia is also reorganizing fundamentally towards organizational goals, which are lean in structure and rich in functionswith business process based on competency network. This organizational arrangement is based on LIPI Regulation No.1 of 2019 concerning SOTK LIPI. Previously, the organizational structure was still rich in structure, less in function, and had a stratified work pattern. The changes in business process after SOTK LIPI applies have a direct impact on science and technology supporting staff who changes that are fundamentally based on functional and competency, are still require adaptation, especially in the clarity of advancing the career of science and technology supporting staff. This research is conducted to analyze the effect of organizational structuring on the happiness of science and technology supporting staff at LIPI.The research method used in this research is explanatory survey. The data analysis technique used to test the model used is multiple linear regression. The respondents are 200 of civil servants as science and technology supporting staff at LIPI. The results of this study indicate that the happiness of civil servants as science and technology supporting staff at LIPI is simultaneously influenced by organizational rearrangement (reorganization) includes restructuring, technology, physical and people settings.